Depth resolved analysis of hydrogen in W7-X graphite components using laser-induced ablation-quadrupole mass spectrometry (LIA-QMS). (January 2019) - Oelmann, Jannis; Li, Cong; Brezinsek, Sebastijan; Rasinski, Marcin; Dhard, Chandra Prakash; König, Ralf; Winters, Victoria; Linsmeier, Christian
Highlights: Graphite limiter tiles from W7-X OP 1.1 are analyzed using residual gas analysis after picosecond laser-induced ablation (LIA-QMS). Hydrogen content measurements are in good agreement with LIBS results. Significant variations of the hydrogen and oxygen contents are observed in poloidal and in toroidal direction. A composition analysis of the residual gas spectrum shows, that hydrocarbons include a significant amount of hydrogen in the residual gas spectrum. Abstract: A deep understanding of the plasma-wall interaction processes in fusion devices like Wendelstein 7-X is necessary for an efficient plasma operation and a long lifetime of the plasma-facing components. In this work we present an approach employing residual gas analysis after picosecond laser-induced ablation (ps LIA-QMS) of graphite limiter tiles, exposed in the first plasma operational phase of Wendelstein 7-X, for depth-resolved and quantitative hydrogen content analysis. A series of poloidal and toroidal locations are analyzed at three of the five limiters, showing up to 2.3 × 10 22 hydrogen atoms/m 2 in net-deposition areas after a total plasma exposure of about 311 s in mixed hydrogen and helium operation. Shallow implantation of hydrogen is observed in erosion zones, where a low fuel content is present due to the high surface temperature during plasma operation. The hydrogen content spans between (1.1 and 3.7) × 10 21 hydrogen atoms/m 2 in the net-erosion areas. Moreover, oxygen has been analyzed and its appearance in both the implantation and deposition zone was verified. Results are compared to thermal desorption spectrometry and to simultaneously performed laser-induced breakdown spectroscopy (LIBS) measurements.